EVALUASI KUALITAS MADU DARI PAKAN SUBTITUSI CAIRAN GULA PASIR PADA LEBAH Tetragonula biroi - Budiaman; Baharuddin; Muhammad Iqbal; Andi Prastiyo (Program Studi Kehutanan Universitas Muslim Maros, 2026)
Stingless bees, particularly Tetragonula biroi, have been widely cultivated in Sulawesi. Beekeeping in urban environments presents different vegetation conditions and sometimes lacks food sources for bees. This study aims to evaluate the quality of T. biroi honey produced by feeding liquid granulated sugar during the nectar-poor season. This study was conducted in Kampung Rimba, Makassar, South Sulawesi, from March to April 2023. Honey quality parameters were evaluated by comparing the results with the Indonesian National Standard (SNI 8664:2018). The results showed that the quality of the honey produced did not all meet SNI standards. The quality that was met was found in the sucrose, with an average of 2.47% and acidity level, with an average of 46.68% NaOH/kg. Other qualities that did not meet were moisture content, with an average of 31.04% and reducing sugar, with an average of 40.85%. These results indicate that sugar substitute feed for T. biroi bees can be used during the lean season. The use or replacement of liquid granulated sugar can only be applied when the beekeeping area lacks nectar food sources.